Design Characteristics to stimulate Technological Appropriation and Student-Centered Design in a VLEs context - Cardoso, Márcia; Silveira, Milene (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
Due to the constant need for improvement in the quality of education, there has been a growing interest in technological tools to support design for teaching and learning in a student-centered way. As a result, the development of these tools has increased. However, it is not clear what shapes teachers’ design decisions and how tools can best support their design processes. Also, researches on Virtual Learning Environments (VLEs) have shown that teachers usually do not explore VLEs to their full potential and only adopt a limited set of available tools. To gain an understanding of this subject, we conducted a systematic review to understand the tools used in education and we ran an online survey with teachers to learn more about the tools they used, why they chose them, and what strengths and weaknesses they found on these tools. That leads us to the primary goal of the present work, which is to explore the VLEs and understand how they can foster technology appropriation and learning design in a student-centered way. Furthermore, a semiotic inspection was performed on the VLEs subject of this study (Moodle and Google Classroom) to analyze the quality of metacommunication between the applications’ designers and the end-users (teachers). Having done that, it was possible to sort out a list of characteristics for the VLEs, aimed to improve appropriation and suit better student-centered design. We hope this work could help to bring (a) clarity about how to boost teacher’s appropriation for future tools and (b) better student outcomes via appropriation and learning design knowledge from (a).